2013
DOI: 10.1002/eat.22114
|View full text |Cite
|
Sign up to set email alerts
|

A placebo‐controlled pilot study of the novel opioid receptor antagonist ALKS‐33 in binge eating disorder

Abstract: Objective: To assess preliminarily the effectiveness of a novel opioid antagonist, ALKS-33, in binge eating disorder (BED).Method: In this randomized, placebocontrolled, flexible dose, proof-of-concept trial, 62 outpatients with BED and obesity received ALKS-33 (N 5 26) or placebo (N 5 36) for 6 weeks. Outcome measures of binge eating, body weight, and eating pathology were assessed.Results: A large decrease in binge eating episode frequency was observed following both ALKS-33 and placebo treatment. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 36 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…Several studies have suggested that these deficits arise from supernormal opioid transmission (Blasio et al 2014; Gorelick et al 2008; Love et al 2009; Mitchell et al 2012; Morganstern et al 2012; Selleck et al 2015; Zubieta et al 1996), and these studies are supported by clinical findings that opioid antagonists have at least some degree of efficacy across several disorders characterized by loss of control over goal-seeking behavior (Cambridge et al 2013; Kim et al 2001; Mitchell et al 2007; Volpicelli et al 1992). However, there is variability in the reports of opiate antagonist clinical efficacy (McElroy et al 2013; Ziauddeen et al 2013), suggesting that further studies are needed to more thoroughly delineate opioid actions within the brain and how normal brain function is influenced by opioid antagonists. The network model outlined in this article suggest that using poly-drug approaches may enhance the efficacy of opiate antagonists in treating disorders such as BED, as well as other conditions such as alcohol dependence, for which opioid antagonists represent one of the only FDA-approved treatments (Pettinati et al 2006; Soyka and Rosner 2008; Volpicelli 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that these deficits arise from supernormal opioid transmission (Blasio et al 2014; Gorelick et al 2008; Love et al 2009; Mitchell et al 2012; Morganstern et al 2012; Selleck et al 2015; Zubieta et al 1996), and these studies are supported by clinical findings that opioid antagonists have at least some degree of efficacy across several disorders characterized by loss of control over goal-seeking behavior (Cambridge et al 2013; Kim et al 2001; Mitchell et al 2007; Volpicelli et al 1992). However, there is variability in the reports of opiate antagonist clinical efficacy (McElroy et al 2013; Ziauddeen et al 2013), suggesting that further studies are needed to more thoroughly delineate opioid actions within the brain and how normal brain function is influenced by opioid antagonists. The network model outlined in this article suggest that using poly-drug approaches may enhance the efficacy of opiate antagonists in treating disorders such as BED, as well as other conditions such as alcohol dependence, for which opioid antagonists represent one of the only FDA-approved treatments (Pettinati et al 2006; Soyka and Rosner 2008; Volpicelli 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant opioid signaling could, therefore, underlie a motivational dysregulation endophenotype that crosses nosological boundaries. Nevertheless, some studies have reported only mixed or limited success with these drugs in the treatment of binge eating [14,15], and, in the case of alcoholism, have suggested a modulating effect of genotype on naltrexone efficacy [7,16,17]. Hence, while there is compelling evidence to suggest the involvement of central opioids in addiction and allied disorders, the mixed clinical results with systemically administered opioid blockers indicate that there are mechanistic complexities that are not yet understood.…”
Section: Introduction: Is Prefrontal Cortex the ‘Undiscovered Countrymentioning
confidence: 99%
“…Two placebo-controlled RCTs have tested different “anti-craving or anti-addiction” medications and have published findings [56;57]. The two published RCTs testing anti-craving medications reported no significant advantage for either acamprosate [56] or for ALKS-33 [57] relative to placebo for any outcome measure, with the later medication resulting in 50% dropout rate.…”
Section: Discussionmentioning
confidence: 99%